Clinico-radiological Profile of Stroke in Western Nepal: A Computed Tomography Study - Acharya, Sumnima; Tiwari, Awadhesh; Shakya, Raju Prasad (Journal of Lumbini Medical College, 2017)
Introduction: Stroke is a major public health burden worldwide and is responsible for a large proportion of disability. It ranks third in the causation of morbidity and mortality. This study was carried out to establish the pattern of various types of cerebrovascular accident (CVA) in western Nepal, to correlate the clinical data and radiological findings in cases of stroke, and to identify the common risk factors associated with stroke. Methods: A total of 200 patients presented at the department of Radio diagnosis from emergency or ward within six months of study period from 18th of September 2015 to 17th of March 2016 with clinical diagnosis of stroke. Brain CT scan was done within 14 days of onset. Results: There were 200 patients with stroke (124 males and 76 females), aged 19 to 92 years in which infarction was more common than hemorrhage (57% Vs 41.5%) clinically. Hypertension was the commonest risk factor noted in 59% cases followed by Diabetes Mellitus in 39%. Middle cerebral artery (MCA) territory infarction was the most common site of infarction. Clinical and CT localization of hemorrhage and infarct was correct in 153 cases (75%) which were statistically significant. Conclusion: Infarction is more common than hemorrhage as the type of stroke. Hypertension is the commonest risk factor followed by diabetes mellitus. J. Lumbini. Med. Coll.Vol 4, No 2, July-Dec 2016 DOI: https://doi.org/10.22502/jlmc.v4i2.91